2014
DOI: 10.1111/liv.12637
|View full text |Cite
|
Sign up to set email alerts
|

In intermediate stage hepatocellular carcinoma: radioembolization with yttrium 90 or chemoembolization?

Abstract: In intermediate HCC stage patients, both treatments resulted in similar survival probabilities despite more advanced disease in the TARE Y-90 group. Still, TARE Y-90 was better tolerated and associated with less hospitalization and treatment sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 39 publications
(72 reference statements)
3
73
0
1
Order By: Relevance
“…The meta-analysis showed that the OS was significantly better in the TARE with Y90 group than in the TACE group. The pooled HR for the (346 patients) (25,(27)(28)(29). The meta-analysis showed that the hospitalization time days was significantly shorter in the TARE with Y90 group than in the TACE group.…”
Section: Overall Survival (Os)mentioning
confidence: 99%
See 4 more Smart Citations
“…The meta-analysis showed that the OS was significantly better in the TARE with Y90 group than in the TACE group. The pooled HR for the (346 patients) (25,(27)(28)(29). The meta-analysis showed that the hospitalization time days was significantly shorter in the TARE with Y90 group than in the TACE group.…”
Section: Overall Survival (Os)mentioning
confidence: 99%
“…Three studies reported the BCLC stage, and more than half of the patients were in BCLC-B stage (24)(25)(26). The median pretreatment MELD score ranged from 7.5 to 10 (23,25,28,29). All the included patients were definitely diagnosed to conform to the eligibility criteria.…”
Section: Hospitalization Time Daysmentioning
confidence: 99%
See 3 more Smart Citations